Radiographic Evaluation of Distal Femoral Sagittal Morphology Following Imageless Robotic-Assisted Total Knee Arthroplasty Using Functional Alignment - Stefano Marco Paolo Rossi; Guglielmo Miele; Angelo Carosini; Paolo Capitani; Francesco Benazzo; Federico Bove; Luca Andriollo (Journal of Clinical Medicine, 2026)
Background: Restoration of native distal femoral sagittal morphology is increasingly recognized as an important goal in total knee arthroplasty (TKA). Alterations in anterior femoral offset (AFO), posterior femoral offset (PFO), and anteroposterior (AP) femoral size may affect knee biomechanics and patellofemoral function. This study evaluated whether imageless robotic-assisted TKA performed using a functional alignment (FA) philosophy resulted in statistically significant preoperative-to-postoperative differences in distal femoral sagittal morphology and coronal alignment. Methods: A retrospective analysis of a prospectively collected database included 250 consecutive primary TKAs performed with the imageless ROSA Knee System (Zimmer Biomet) using a tibia-first FA workflow. Preoperative and postoperative radiographic measurements included mechanical hip–knee–ankle angle (mHKA), medial proximal tibial angle (MPTA), lateral distal femoral angle (LDFA), AP femoral size, AFO, and PFO. Paired comparisons were performed using appropriate statistical tests. Results: While no statistically significant differences were observed between preoperative and postoperative mean values for overall mechanical alignment (mHKA) (177.1 ± 7.7° vs. 177.3 ± 3.2°, p = 0.11), secondary coronal parameters demonstrated statistically significant controlled adjustments reflecting the patient’s individualized functional alignment. No significant differences were observed in sagittal morphology: AP femoral size (70.7 ± 6.3 vs. 71.0 ± 6.2 mm, p = 0.31), AFO (10.7 ± 5.9 vs. 10.8 ± 5.8 mm, p = 0.70), and PFO (34.1 ± 7.6 vs. 34.5 ± 7.2 mm, p = 0.24). Conclusions: Imageless robotic-assisted TKA performed with an FA philosophy and a tibia-first workflow demonstrated minimal mean preoperative-to-postoperative changes in distal femoral sagittal parameters at the cohort level. While overall mean mechanical alignment remained unchanged, secondary coronal parameters showed controlled, statistically significant adjustments, reflecting the implementation of an individualized three-dimensional alignment strategy. These findings support robotic FA as a patient-specific three-dimensional alignment strategy. Further prospective studies are needed to determine whether these radiographic results translate into improved clinical outcomes.